Jordanian Public University Students’ Reliance on Social Networks as a Source of Information on University Education during Covid- 19 Pandemic: A Field Study - Nejadat , Ali; Sharadqah, Saja Abdullah (Jordan Journal of Social Sciences, 2023)
This study seeks to understand the reliance of Jordanian public university students on social media networks as a source of information about university education during the Corona pandemic. By employing a questionnaire, this research has surveyed a sample of (450) individuals from the study population which consists of all students from three universities: Yarmouk University, The University of Jordan, and Mu’tah University, with (150) students from each of these universities. According to the findings, most of the respondents have shown a reliance on social media networks as a source of university education during the pandemic. Facebook is the most relied on online platform by students given that social media networks have helped Jordanian university students in identifying the latest decisions and official news regarding university education during the pandemic. The findings report a high level of cognitive effects in Jordanian university students that are resulted from the reliance on social media networks. These online platforms have provided the respondents with the most recent information and regulations about university education. Furthermore, the outcomes reveal an average direct correlation between the Jordanian public university students’ reliance on social media networks and their trust in these platforms as a source of information about university education.